RECONSTRUCTION REGULATIONS OF ASSET RECOVERY IN CORRUPTION CASE TOWARDS THE STATE FINANCES AND ECONOMY RESTORATION - QOHAR AF, ABDUL (Jurnal Independent, 2023)
Abstract In fact, the main objective of eradicating Corruption is to reco ver state losses. One of the elements of corruption in Article 2 and Article 3 of Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 concerning the Eradication of Corruption (UU Tipikor) is an element of state financial loss, this element has a cons equence that the eradication of corruption is not only aimed at deterring corruptors through heavy imprisonment but also restoring state finances due to corruption as emphasized in the preamble and general explanation of the Corruption Act. Failure to retu rn the proceeds of corruption can reduce the meaning of â€œ punishing the corruptors â€ itself.